Improved gas separation performance of PMMA/Matrimid@5218/graphene oxide (GO) mixed matrix membranes - Amirali Salehi; Mohammadreza Omidkhah; Abtin Ebadi Amooghin; Mohammad Mehdi Moftakhari Sharifzadeh (Journal of CO2 Utilization)
In recent membrane research, the search for physicochemically stable membranes with exceptional separation properties surpassing the Robson upper limit has attracted considerable attention. For this purpose, the use of polymer blending and mixed matrix membranes (MMMs) has shown promise in improving membrane performance. In this study, we fabricated a blend membrane by incorporating Poly (5 amino-1-(4 aminophenyl)-1,3-trimethyl indane) (Matrimid@5218) into the poly(methyl methacrylate) (PMMA) polymer matrix to harness the positive properties of Matrimid, such as high mechanical strength and thermal stability, along with the suitable permeability and selectivity of PMMA. Subsequently, graphene oxide (GO) was embedded into this blend membrane to explore the gas separation properties of these new MMMs, focusing on He/N2, He/CH4, CO2/N2, and CO2/CH4 separations. After identifying the optimal polymer blend composition, gas permeation experiments were conducted on MMMs with varying filler loadings at different pressures (2–10 bar) and temperature (35 ºC). Comprehensive characterization techniques, including FTIR, DSC, TGA, SEM, XRD, and tensile testing, were employed to assess the prepared membranes. The results revealed that PMMA/10 %Matrimid/1 %GO exhibited the highest performance for He/N2 and He/CH4 separations. Notably, the He permeability increased from 12.83 Barrer for the pure PMMA membrane to 21.19 Barrer in PMMA/10 %Matrimid/1 %GO (about 65 %). Also, He/N2 and He/CH4 selectivities of PMMA/10 %Matrimid/1 %GO reached 857.9 and 1033.66. On the other hand, PMMA/10 %Matrimid/2 %GO emerged as the optimal MMM for CO2/N2 and CO2/CH4 separation. This MMM exhibited CO2 permeability, CO2/N2, and CO2/CH4 selectivities of 14.23 Barrer, 729.74, and 862.42, respectively. Comparing these results to the pure PMMA membrane with CO2 permeability of 1.08 Barrer, CO2/N2 selectivity of 31.76, and CO2/CH4 selectivity of 83.07, PMMA/Matrimid/GO MMM series were good candidates for further investigation in industrial gas separations.